Preparation of NiAl2O4-Based Flexible Substrates for Metamaterials with Negative Dielectric Properties. Issue 1 (December 2018) - Rahman, Md; Ahamed, Eistiak; Faruque, Mohammad; Islam, Mohammad
Abstract Various techniques are commonly used to produce nano-crystalline NiAl2 O4 materials; however, their practical applications in the microwave region remain very limited. In this work, flexible substrates for metamaterials containing two different concentrations of NiAl2 O4 (labelled Ni36 and Ni42 ) have been synthesised using a sol-gel method. The formation of spinel structures in the synthesised materials is confirmed, and their crystalline sizes are determined using scanning electron microscopy, X-ray diffraction, and energy dispersive X-ray techniques. The dielectric properties, conductivities, loss tangents, and other parameters of the NiAl2 O4 -based substrates are analysed to evaluate their applicability as dielectric materials for the microwave frequency range. The obtained results show that the fabricated Ni36 and Ni42 nickel aluminates possess dielectric constants of 4.94 and 4.97 and loss tangents of 0.01 and 0.007, respectively; in addition, they exhibit high flexibility and light weight, which make them suitable for applications as metamaterial substrates. The synthesised structures are also validated experimentally using a commercially available electromagnetic simulator; as a result, double negative behaviour of the flexible metamaterials has been observed. Furthermore, it is found that the prepared NiAl2 O4 substrates can be used in the S-, C-, and X-bands of the microwave frequency region.